2018
DOI: 10.1002/jcla.22598
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum rheumatoid factor level and no‐reflow phenomenon in patients with acute ST‐segment elevation myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: Baseline serum RF concentrations are independently associated with the no-reflow phenomenon in patients undergoing primary PCI for acute STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It should be noted, nonetheless, that a wide variety of demographic, laboratory, and procedural factors have been proven to influence the development of NR. [20][21][22][23][24] Several studies have shown a link between AF-related stroke risk scoring systems, which are often used in cardiology, and NR in acute MI patients. Independent of AF and stroke risks, the impact of stroke risk scoring system components on coronary artery events was also examined.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, nonetheless, that a wide variety of demographic, laboratory, and procedural factors have been proven to influence the development of NR. [20][21][22][23][24] Several studies have shown a link between AF-related stroke risk scoring systems, which are often used in cardiology, and NR in acute MI patients. Independent of AF and stroke risks, the impact of stroke risk scoring system components on coronary artery events was also examined.…”
Section: Discussionmentioning
confidence: 99%
“…Higher B-type natriuretic peptide, high-sensitivity C-reactive protein, and systemic immune inflammation index values were found to be associated with NR. 35,36 Quisi et al 37 determined a close relationship between baseline serum rheumatoid factor and NR phenomenon in patients with acute STEMI. Cheng et al 16 demonstrated higher levels of d -dimer and cystatin C in patients with NR in their study consisting of 218 patients with acute anterior MI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between RF and the prognosis and treatment of ischemic stroke is still not extensively studied. RF has been associated with cardiovascular diseases [ 97 , 98 ], immune complexes (ICs) and complement-mediated inflammation [ 99 ], as well as endothelial dysfunction [ 29 ]. Positive RF status has been linked to increased risks and poor prognosis of cardiovascular diseases [ 53 , 100 104 ].…”
Section: Rheumatoid Factor and Il-6 Inhibition In Ischemic Stroke: Cu...mentioning
confidence: 99%